THE INFLUENCE OF PARENTING AND INDEPENDENCE PATTERNS ON THE DEVELOPMENT OF EARLY CHILDHOOD EXECUTIVE FUNCTIONS - Triastutik, Mei; Susanti, Debie (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Early childhood is the age where children experience very rapid development. Therefore it is important for them to get all the best in order to achieve optimal development. This research was conducted to provide an overview of 1) The effect of parenting style on the development of executive function in early childhood 2) The effect of independence on the development of executive function in early childhood. 3) The effect of parenting and independence on the development of executive functions in early childhood. This research uses quantitative methods. This research was conducted because the effect of parenting and independence on the executive function of group A children in West Java Province had never been investigated. As for the processing and collection of data is done through multi random sampling . The subjects in the study were children aged 4-5 years from the same area with different parenting styles. The research location is a kindergarten in the city of Bekasi - West Java. As a result, parenting and independence have a very important role for the development of executive function early childhood.